Tensile strength of reinforced laminates after oblique ballistic impact: an experimental study - Randjbaran, Elias; Abdul Majid, Dayang Laila; Sultan, MTH; Mazlan, Norkhairunnisa (Sage Publications, 2022)
The present study endeavoured to examine the tensile strength of the laminates, which were made of carbon/Kevlar hybrid reinforced fibre with carbon nanotubes (CNTs) post oblique impacts. Although a number of experimental investigations on tensile properties of CNTs have been already performed, the coupling effects of CNTs and oblique impacts on tensile strength have yet to be reported. Due to the superior elastic modulus, the advanced nano-fillers were chosen as reinforcement of the carbon/Kevlar hybrid fibre. The inter-ply woven fabric possess high strength and excellent toughness due to the carbon and Kevlar fibre respectively and therefore well suited for ballistic impact applications. In spite of the fact that the effects of direct impact is most detrimental and widely reported, the effect of nano-fillers on the tensile integrity of oblique impacted specimens are of primary interest as most impact events are random in nature. CNTs with 0.1–1.5% loading ratios are dispersed into the epoxy resin and intra-ply Carbon Kevlar hybrid fabrics composite plates are fabricated via hand layup process. A loading of minimum 0.1% to maximum 1.5% CNTs were dispersed into liquid epoxy resin. The reinforced epoxy resin was applied to carbon/Kevlar fabric composite by layup process. Inclusion of CNT revealed depreciating mechanical properties in terms of tensile toughness; however, the inclusion demonstrated a potential reinforcement in a high modulus/strength in composite laminate’s specimens. Findings indicated that 0.7% of CNT had maximum tensile toughness values; whereas, the highest values of Young modulus were followed by tensile strength at 1.5% CNT. Moreover, compared with other factors, the impact load had a great influence on its specimens’ strength, and the effects of angled targets on the impact load of the specimens as well as CNTs' value were mostly obvious. Consequently, this investigation may be considered as a practical basis for designing and optimising of CNT contents and possible angle degrees and analysing tensile behaviour after the impact events.